2014
DOI: 10.1017/etds.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Positive topological entropy for monotone recurrence relations

Abstract: We associate the topological entropy of monotone recurrence relations with the Aubry-Mather theory. If there exists an interval [ρ 0 , ρ 1 ] such that, for each ω ∈ (ρ 0 , ρ 1 ), all Birkhoff minimizers with rotation number ω do not form a foliation, then the diffeomorphism on the high-dimensional cylinder defined via the monotone recurrence relation has positive topological entropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It was shown by Mramor and Rink [2013] that under some conditions, each minimizer is either Birkhoff, or it is oscillating and exponentially growing. We proved in [Guo et al, 2014] that this conclusion holds true even if we relax the strong twist condition in [Mramor & Rink, 2013]. Precisely, we showed that for the one-dimensional generalized FK model each minimizer with bounded action is Birkhoff.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It was shown by Mramor and Rink [2013] that under some conditions, each minimizer is either Birkhoff, or it is oscillating and exponentially growing. We proved in [Guo et al, 2014] that this conclusion holds true even if we relax the strong twist condition in [Mramor & Rink, 2013]. Precisely, we showed that for the one-dimensional generalized FK model each minimizer with bounded action is Birkhoff.…”
Section: Introductionmentioning
confidence: 83%
“…We should mention that for high-dimensional FK model, whether the minimizer x itself is Birkhoff is still unclear, although it is for the onedimensional case, see [Guo et al, 2014;Mramor & Rink, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that Proposition 2.5 has provided great convenience to determine whether the system has positive topological entropy, which has been applied in [2,3,16,21,22,24] under different background and conditions.…”
Section: Preliminariesmentioning
confidence: 99%
“…If the monotone recurrence relation of equation (1.1) has a generating function, then zero topological entropy implies that Birkhoff minimizers with each rotation number form a continuous foliation [19]. Our first topic in this paper is to investigate, for the general monotone recurrence relations, the properties of rotation sets of equation (1.1) with zero topological entropy.…”
Section: Introductionmentioning
confidence: 99%